A rapid evidence assessment of recent therapeutic touch research. Issue 5 (20th March 2021) - Garrett, Bernie; Riou, Marliss
Abstract: Aim: To synthesize the most recent evidence investigating the effectiveness and safety of therapeutic touch as a complementary therapy in clinical health applications. Design: A rapid evidence assessment (REA) approach was used to review recent TT research adopting PRISMA 2009 guidelines. Methods: CINAHL, PubMed, MEDLINE, Cochrane databases, Web of Science, PsychINFO and Google Scholar were screened between January 2009–March 2020 for studies exploring TT therapies as an intervention. The main outcome measures were for pain, anxiety, sleep, nausea and functional improvement. Results: Twenty‐one studies covering a range of clinical issues were identified, including 15 randomized‐controlled trials, four quasi‐experimental studies, one chart review study and one mixed methods study including 1, 302 patients. Eighteen of the studies reported positive outcomes. Only four exhibited a low risk of bias. All others had serious methodological flaws, bias issues, were statistically underpowered and scored as low‐quality studies. No high‐quality evidence was found for any of the benefits claimed.